Sosialisasi Strategi Mencegah Investasi Bodong Melalui Literasi Keuangan Bagi Ibu-ibu PKK Kelurahan Gayamsari Semarang - Scorina Dwiantari; Irene Nathalia Setiawan; Rusdiana Permanasari; Linda Novasari (Lembaga Pengembangan Kinerja Dosen, 2025)
Fraudulent investment is a phenomenon that has become widespread among Indonesian society. The PKK mothers in Rt 5 Rw 2, Gayamsari sub-district, have not yet gained any knowledge or understanding about the dangers of fraudulent investments and their characteristics, nor have they received any knowledge or understanding related to financial literacy that could protect their families from the dangers of fraudulent investments. The PKK of Gayamsari sub-district urgently needs socialization on strategies to prevent being affected by fraudulent investments and to recognize the signs of such investments. In addition to fraudulent investments, they also feel the need to receive socialization about financial literacy and the characteristics of legal and safe investments, so that they can prevent becoming victims of fraudulent investments. Based on the problems that occur, solutions are needed to address them. The purpose of this community service activity is to provide understanding and knowledge about financial literacy so as not to fall into fraudulent investments. Partners are also given an understanding of safe and legal investments to avoid the dangers of fraudulent investments. The expected outcome of this service activity for the mothers of the PKK in Gayamsari sub-district is to understand the importance of financial literacy and the dangers of fraudulent investments along with their characteristics. It is hoped that the PKK mothers in Gayamsari sub-district will be wise in managing family finances by choosing safe investments for the future of their household and family, as well as being able to prevent becoming victims of fraudulent investment scams.